Hyperkalemia-induced secondary hyperaldosteronemia : a complex model of integrative research - Fazan, Frederico Sassoli [UNIFESP] (2020)
High potassium in the blood, also known as hyperkalemia, can induce intense aldosterone secretion through membrane voltage-dependent mechanisms. Aldosterone is known to enhance potassium excretion, however recent studies have suggested that aldosterone may not be necessary for potassium balance in some conditions, challenging the necessity of aldosterone as a regulator of potassium homeostasis. Furthermore, aldosterone increases during dietary sodium restriction, activating aldosterone-sensitive (HSD2) neurons promoting sodium appetite, but aldosterone is not necessary for the activation of these neurons, suggesting that another stimulus is necessary. Potassium consistently elevates during prolonged or severe dietary sodium restriction which may enhance neuronal activity. The aim of this study was to characterize and use an animal model to increase aldosterone levels by elevating potassium concentration in the blood via intragastric administration of high doses of potassium chloride. With this model, we characterized the chronic and acute clearance rate of a high KCl administration in awake and anesthetized rats. We also closely examined the effect of the intragastric KCl administration on the electrocardiogram and arterial blood gas and other chemical parameters before and after KCl treatment to precisely determine the physiological stress of this model. Furthermore, we examined the necessity of aldosterone using the mineralocorticoid receptor antagonist spironolactone in the intense and acute hyperkalemia in rats. Finally, we analyzed the influence of blood levels of potassium on the activation of HSD2 neurons in the NTS and on sodium appetite elicited by sodium deprivation in combination with either dietary supplementation or restriction of potassium from data obtained previously. Intragastric KCl administration had a profound impact on urinary sodium and potassium excretion and produced an intense diuresis. Blocking MR did not change how potassium was handled when acute hyperkalemia was present, but delayed recovery at lower serum potassium values. In anesthetized rats, KCl administration greatly impacted the ECG. Glucose intolerance was related to increasing the risk of death by intragastric potassium KCl load in anesthetized rats. Furthermore, potassium changes in the ECF were found to not interfere with the activation of HSD2 neurons or generation of sodium appetite in rats.